Cultural competence or speaking the patientâ€™s language - Vanessa Burch (South African Medical Association, 2016)
Cultural competence has become yet another buzz word in the education of healthcare professionals. According to Prasad et al.,Â â€˜culturally competent care assumes that healthcare providers can learn a quantifiable set of attitudes and communication skills that will allow them to work effectively within the cultural context of the patients they come acrossâ€™. The questions that arise, therefore, are whether clinical trainees are being fully supported to acquire this fundamental skill and whether overloaded curricula can accommodate the ongoing demand for more â€˜teaching timeâ€™.Â